African International Legal Histories – International Law in Africa: Perspectives and Possibilities - Jakob Zollmann (Leiden Journal of International Law, 2018)
Hitherto, the `African part' of the history of international law has often been limited to the (critical engagement with) `the acquisition of Africa' since the 1880s and questions of `state succession' and international borders following independence starting in the 1950s. In this historical narrative, the dominance of colonialism is evident. It seems that `Africa' as a narrative concept in international legal history remains tied to abstract contrasts such as `foreign domination' versus `independence', or `exploitation' versus `development'. However, if twenty-first century writings about `international law in Africa' and its histories remain shaped by this perspective, historians may lose sight of issues, questions, or ideas formed in historical Africa that do not fit into this preconceived dichotomous matrix. After discussing methodological challenges, this article asks for other `contacts', other arenas of `internationality' and international law in Africa's pre-colonial past. These contacts reach back very far in history. Three arenas are mentioned: the Red Sea area and Ethiopian-Arab relations; the Indian Ocean rim; and finally, the case of nineteenth-century Ethiopia.
Keywords: 330; Africa; Ethiopia; history; international law; presentism